Alpha-Lipoic Acid Downregulates IL-1β and IL-6 by DNA Hypermethylation in SK-N-BE Neuroblastoma Cells - Simona Dinicola; Sara Proietti; Alessandra Cucina; Mariano Bizzarri; Andrea Fuso (MDPI AG, 2017)
Alpha-lipoic acid (ALA) is a pleiotropic molecule with antioxidant and anti-inflammatory properties, of which the effects are exerted through the modulation of NF-kB. This nuclear factor, in fact, modulates different inflammatory cytokines, including IL-1b and IL-6, in different tissues and cell types. We recently showed that IL-1b and IL-6 DNA methylation is modulated in the brain of Alzheimer's disease patients, and that IL-1b expression is associated to DNA methylation in the brain of patients with tuberous sclerosis complex. These results prompted us to ask whether ALA-induced repression of IL-1b and IL-6 was dependent on DNA methylation. Therefore, we profiled DNA methylation in the 5'-flanking region of the two aforementioned genes in SK-N-BE human neuroblastoma cells cultured in presence of ALA 0.5 mM. Our experimental data pointed out that the two promoters are hypermethylated in cells supplemented with ALA, both at CpG and non-CpG sites. Moreover, the observed hypermethylation is associated with decreased mRNA expression and decreased cytokine release. These results reinforce previous findings indicating that IL-1b and IL-6 undergo DNA methylation-dependent modulation in neural models and pave the road to study the epigenetic mechanisms triggered by ALA.